Quantification of tension in Thera-Band® and Cando® tubing at different strains and starting lengths - Thomas, M.; Müller, T.; Busse, W. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Elastic resistance exercise is frequently used in rehabilitation programs. Precise quantification using color coded bands is not possible. A method to predict forces for any length of mostly used elastic tubings and thereby a general equation for the comparison of elastic material is presented. Methods: In an in vitro-series the tubing tension in relation to elongation of 6 colors of Thera-Band® and Cando® tubings was directly measured. The relation between tension and elongation was determined depending on different resting lengths. In clinical practice tension and elongation are prescribed. Two mathematical methods to calculate the resting length as regulatory variable are presented. One is based on the construction of iso-tension curves, the 2nd on the general mathematical relation d % tension=K* % length change+n. Results: 1. The tension/elongation relation is linear beyond a threshold in the early part of elongation. 2. The iso-tension method works graphically and faciliates the precise determination of resting length. 3. The double % relation between tension and elongation method describes the general properties of all tubings, where K=0.75 is a general constant. To calculate absolute values for the resting length, corresponding to a given tension and elongation, special ''color constants² are presented. Conclusion: The prediction of maximum tension values for any given elongation is possible by simple varation of resting length. These findings may improve the usefulness of elastic tubings in rehabilitation programs. The mathematical method further may be used for the comparison of elastic materials with linear characteristics.